FORMULATION AND IN-VITRO EVALUATION OF ORAL SUSTAINED RELEASE DRUG DELIVERY SYSTEM FOR LAMIVUDINE MATRIX TABLETS USING METHOCEL K15M CR POLYMER - Md. Mofizur Rahman; Md. Qamrul Ahsan; Abul Bashar Ripon Khalipha; Md. A. K. Azad; Nazneen Ahmeda Sultana; Sophia Hossain; Sanjida Haque (European Scientific Journal, ESJ, 2014)
PURPOSE: The present work reports the study of different proportion of Lamivudine: Methocel K15M formulations, inorder to investigation the effect of polymer proportion and diluent on the drug release mechanism. Lamivudine, an anti-HIV agent, was used as a model drug to evaluate its release characteristics from different matrices. METHOD: Matrix tablets of Lamivudine were prepared by direct compression process using methocel K15M CR polymer. In vitro release studies were performed using US Pharmacopeia type 1 apparatus (basket method) in 900 mL of pH 6.8 phosphate buffer at 100 rpm for 8 hours (Initial 2 hours in simulated gastric fluid (pH 1.2)). Scanning Electron Microscopy (SEM) was used to evaluate and surface properties of the matrices. Drug release was analyzed according to their kinetic models. A one-way analysis of variance (ANOVA) was used to interpret the results. RESULTS: Statistically significant differences were found among the drug release profile from different formulations. Higher proportion of polymeric content (25 to 30% of the total tablet weight) in the matrix, release was extended > 8 hours due to increased tortuosity and decreased porosity. At lower proportion of polymeric content (10% of the total tablet weight), the rate of drug release was elevated. Two formulations showed drug release is more controlled. The release mechanism was explored and explained with zero order, first order, Higuchi and Korsmeyer and Hixon-Crowell equations. CONCLUSION: The results generated in this study showed that the profile and kinetics of drug release were functions of polymer type, polymer level and physico-chemical properties of the drug. By suitable modulation could be developed controlled delivery of such type of drug.